2003
DOI: 10.1103/physrevlett.90.067002
|View full text |Cite
|
Sign up to set email alerts
|

Doubled Full Shot Noise in Quantum Coherent Superconductor-Semiconductor Junctions

Abstract: We performed low temperature shot noise measurements in superconductor (TiN) -strongly disordered normal metal (heavily doped Si) weakly transparent junctions. We show that the conductance has a maximum due to coherent multiple Andreev reflections at low energy and that the shot noise is then twice the Poisson noise (S = 4eI). When the subgap conductance reaches its minimum at finite voltage the shot noise changes to the normal value (S = 2eI) due to a large quasiparticle contribution.PACS numbers: 74.40.+k, 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
76
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 19 publications
(37 reference statements)
4
76
0
Order By: Relevance
“…Examples include the information on electron kinetics, 1 quantum statistics of charge carriers, 2 correlations of electronic wave functions, 3 and effective quasiparticles charges. 4,5 Noise spectra can also be used to reconstruct quantum states via a series of measurements known as quantum state tomography. 6 Conventionally, evaluations of noise spectra are largely limited to the rather low frequency ( ω ≪ k B T ), where the noise spectrum is symmetric at zero bias.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include the information on electron kinetics, 1 quantum statistics of charge carriers, 2 correlations of electronic wave functions, 3 and effective quasiparticles charges. 4,5 Noise spectra can also be used to reconstruct quantum states via a series of measurements known as quantum state tomography. 6 Conventionally, evaluations of noise spectra are largely limited to the rather low frequency ( ω ≪ k B T ), where the noise spectrum is symmetric at zero bias.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, shot noise can be used to determine the quanta of the electric charge of the current carriers in conducting materials [2]. Indeed, it has been used to characterize the nature of Cooper pairs in superconductors [3] and the fractional charge of the quasiparticles of the quantum Hall effect [4]. For low voltages, the noise in the current is thermal and is called Johnson-Nyquist noise [5,6].…”
mentioning
confidence: 99%
“…We have shown that current noise measurements provide a precise description of electronic transport in Josephson junctions. Having now a clear description of the current noise in diffusive S/N/S junctions and in diffusive S/N contacts [35,36], we are now addressing the problem of crossed correlations in multi-terminal superconducting hybrid nanostructures. The idea is to fabricate a normal nanostucture that is connected to one or several superconducting electrodes.…”
Section: Discussionmentioning
confidence: 99%